The Effect of Applying The Bil-Qolam Method on The Reading Quran Ability of Elementary School Students - Akhmad Mukhlis; Shobahul Mufidah; Machsunah Machsunah; Afif Aulia Nurani (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
This study aims to describe the application of bil-qolam in learning the Qur'an for elementary school age students (SD) and its effect on the ability to read the Qur'an. An experimental quantitative approach was used in this study involving 40 students in grade 4, consisting of grades 3 and 4 of elementary school. Research subjects were divided into two groups as experimental and control groups. The results of this study indicate that the application of the bil-qolam method is considered effective in increasing students' competence in reading the Qur'an, especially in the fields of tajwid, fashohah and langgam. The data obtained from the Mann-Whitney non-parametric test that has been carried out by researchers, namely the average post-test score of the experimental group has an increase in the arithmetical average of 17.85 and the control group has an increase in the pre-test. This proves that the bil-qolam method has an effect on improving the ability to read the Qur'an for elementary school age students.